Combined transcranial alternating current stimulation and continuous theta burst stimulation: a novel approach for neuroplasticity induction. (7th January 2016) - Goldsworthy, Mitchell R.; Vallence, Ann‐Maree; Yang, Ruiting; Pitcher, Julia B.; Ridding, Michael C.
Abstract: Non‐invasive brain stimulation can induce functionally relevant plasticity in the human cortex, making it potentially useful as a therapeutic tool. However, the induced changes are highly variable between individuals, potentially limiting research and clinical utility. One factor that might contribute to this variability is the level of cortical inhibition at the time of stimulation. The alpha rhythm ( 8–13 Hz) recorded with electroencephalography (EEG) is thought to reflect pulsatile cortical inhibition; therefore, targeting non‐invasive brain stimulation to particular phases of the alpha rhythm may provide an approach to enhance plasticity induction. Transcranial alternating current stimulation (tACS) has been shown to entrain cortical oscillations in a frequency‐specific manner. We investigated whether the neuroplastic response to continuous theta burst stimulation (cTBS) was enhanced by timing bursts of stimuli to the peak or the trough of a tACS‐imposed alpha rhythm. While motor evoked potentials (MEPs) were unaffected when cTBS was applied in‐phase with the peak of the tACS‐imposed oscillation, MEP depression was enhanced when cTBS was applied in‐phase with the trough. This enhanced MEP depression was dependent on the individual peak frequency of the endogenous alpha rhythm recorded with EEG prior to stimulation, and was strongest in those participants classified as non‐responders to standard cTBS. These findings suggest that tACS may be used in combination with cTBS to enhance the plasticity response. Furthermore, the peak frequency of endogenous alpha, as measured with EEG, may be used as a simple marker to pre‐select those individuals likely to benefit from this approach. Abstract : We investigated whether the neuroplastic response to cTBS was enhanced by timing the bursts of stimuli to different phases of a tACS‐imposed alpha oscillation. We show that the response to cTBS was enhanced when stimulus bursts were delivered in‐phase with the trough, but not the peak, of the applied current. This enhancement of the cTBS response was dependent on the individual peak frequency of the endogenous alpha rhythm, and was strongest in non‐responders to standard cTBS.